Perancangan Website Penjualan Cupang Menggunakan Laravel( Studi Kasus Salatiga Betta Genetic) - Arbitra Satria Perdana; Evangs Mailoa (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
Salatiga Betta Genetic is a shop that sells betta fish products. This store is known to still use conventional sales methods, namely by coming to the place and promoting products through various social media because it does not yet have a sales system itself. Sales activities like this can cause problems in managing order data from customers on various social media. Therefore, a website-based betta fish sales information system was built. The sales system will be built with the Laravel framework and using the RAD (Rapid Application Development) method in order to get maximum results but it doesn't take long. The result of the research is a betta fish sales website that can help Salatiga Betta Genetic in managing orders and can help reach a wider market